A Suggested Framework to Face the Challenges of E-Learning 'Corona Epidemic (Covid-19) as a Sample' - Mohammed Owda; Niveen Hills; Assma Mosa (Umm Al-Qura University, 2022)
The aim of the research was to present a suggested Framework to face the challenges of e-learning in light of the Corona epidemic (Covid-19), The researchers followed the descriptive analytical approach to achieve the objectives of the study, as e-learning challenges scale was prepared as a study tool. The scale was consisted of (24) indicators distributed over five disciplines, and the study tool was applied on a random sample of (50) teachers. The study results showed that the e-learning challenges were in the middle. The research recommended of the necessity of improving and training the students and the teachers on creative use to the unified educational platforms in e-learning process, and holding workshops for parents and students to raise their awareness of the importance of e-learning.